Building Condition Assessment In School Using JKR Standard - Abdul Rahman, Mohammad Ashraf; Abdul Manan, Abdul Wafiy Naqiuddin (Progress in Engineering Application and Technology, 2020)
Assessment of building conditions is increasing and gaining significance in. Building condition assessment is a real time assessment to gives information of defects and problems issue of the building. The primary purpose of performing a building inspection is to evaluate the building’s condition. Through building inspection , a diagnostic can be made in which sector of the building having the most defects. An analysis to the building diagnostics gives confirmation of defects. Also, building condition assesement is the priority key to investigate history of defects prior to whole system in the building. This study involve in three school located in putatan districs. The methodology of this research is using JKR standard building condition assessment form of each defect in civil , electrical and mechanical system in the building. The trend of damage in civil , electrical and mechanical after the analysis.